Histological Classification and Immunohistochemical Evaluation of MDM2 and CDK4 Expression in Canine Liposarcoma. (July 2016) - Avallone, G.; Roccabianca, P.; Crippa, L.; Lepri, E.; Brunetti, B.; Bernardini, C.; Forni, M.; Olandese, A.; Sarli, G.
Canine liposarcoma is an uncommon soft tissue sarcoma usually arising in the subcutis. While liposarcoma classification in dogs is based solely on histology, in humans it depends on the detection of genetic abnormalities that can lead to specific protein overexpression. This study is an immunohistochemical evaluation of MDM2 and CDK4 expression in canine liposarcoma designed to assess the correlation of these proteins with histologic type, grade, mitotic index and Ki67 labeling index and evaluate their utility in improving tumor classification. Fifty-three liposarcomas were retrospectively collected: 24 were well differentiated liposarcomas (WDL), 16 of which expressed MDM2 and 21 CDK4; 7 were myxoid liposarcomas (ML), 1 of which expressed MDM2 and 5 expressed CDK4; 18 were pleomorphic liposarcomas (PL), all were MDM2 negative and 12 expressed CDK4. Four tumors were morphologically consistent with dedifferentiated liposarcoma (DDL) a subtype described only in humans: 3 expressed MDM2 and 4 expressed CDK4. MDM2 expression correlated with histotype (highly expressed in WDL and DDL) and grade (highly expressed in grade 1 tumors). Histotype correlated with the Ki67 labeling index (lowest in WDL and highest in DDL). A revised classification, considering MDM2 expression, allowed 8 WDL to be reclassified as PL and correlated significantly with mitotic and Ki67 labeling index (both significantly lower in WDL and progressively higher in ML and DDL). These results partially parallel data reported for human liposarcomas, suggesting that WDL and DDL are distinct neoplastic entities characterized by MDM2 expression, which may represent a useful diagnostic and potentially prognostic marker for canine liposarcoma.